Disconnection vs excision? A ten year review of hypothalamic hamartomas. (31st January 2018) - Pasricha, Ribhav; Siddiqui, Saquib Azad; Suri, Ashish; Borkar, Sachin; Mahapatra, Ashok K
Abstract: OBJECTIVE: Hypothalamic hamartomas (HH) are rare tumors of childhood. They are usually associated with gelastic seizures. The optimal management of these tumors lacks a consensus. We present our experience with hypothalamic hamartomas over a ten year period. METHODS: This study presents a retrospective review of 16 patients with HH's treated between 2002 and 2012 at the All India Institute of Medical Sciences (AIIMS), New Delhi, India, a tertiary care neurosurgical centre. RESULTS: There were 16 patients with an age ranging from 1.5 years to 20 years and included 9 males and 7 females. The most common symptom was seizures (81%; gelastic seizures-62.5%) followed by precocious puberty (56.2%). The median tumor volume was 5.9 cc (range 1.3 to 108 cc). Fourteen patients underwent surgery while two were managed conservatively. Three patients received secondary Gamma Knife therapy. A good seizure outcome (Engel class I and II) post surgery was seen in 8 (50%) patients. The median follow up period was 39 months (range 1 to 114 months). The odds ratio for a better seizure outcome was 2.5 times more in disconnection than for excision. The symptoms of precocious puberty had resolved in 7 of the 9 affected patients (78%). Transient diabetes insipidus was seen in one (6.2%) patient postoperatively while hyperphagia was noted in four (25%) patients. Hyperphagia persisted in all four patients until last follow up. CONCLUSIONS: HHs present with gelastic seizures or precocious puberty. Disconnection of the HH is more effective and a safer procedure vis-a-vis excision for controlling seizures.